The first report of the reaction of Davy's reagent with [CpMo(CO)(n)](2) (n=2,3) via a phosphorus-sulfur bond cleavage process. Isolation and characterization of CpMo(CO)(2)(S2P(SPhMe)(2)), Cp2Mo2(CO)(5)(S2P(SPhMe)) and Cp2Mo2(mu-S)(mu-S-2)(mu-SPhMe) (Cp = (eta(5)-C5H5)) - Wong, R.C.S.; Ooi, M.L.; Ng, S.W.; Thomas, N.F. (Elsevier, 2010)
The reaction of [CpMo(CO)(3)](2) (1) and its congener, the triply bonded [CpMo(CO)(2)](2) (2) with 2,4-bis(p-tolylthio) 1,3-dithia-2,4-diphosphetane-2,4-disulfide (DR, Davy's reagent) in toluene at 110 and 70 degrees, respectively, led to the isolation of dark brown solids of CpMo(CO)(2)(S2P(SPhMe)(2)) (3), deep pink solids of Cp2Mo2(CO)(5)(S2P(SPhMe)) (4) and dark purple solids of Cp2Mo2(mu-S)(mu S-2)(mu-SPhMe) (5) with yields dependent on reaction conditions. Thermolytic studies followed by H-1 NMR indicated that 3 and 4 had degraded to 5. The postulated mechanism involves P-S bond cleavage in DR leading to a ring opening and desulfurization process. (C) 2010 Elsevier B. V. All rights reserved.